A study of Solvent and Antisolvent Influence on the Crystal Morphology of ϵ‐CL‐20 by a Modified Attachment Energy Model. Issue 7 (3rd April 2020) - Zhao, Li; Li, Jing; He, Jinxuan; Luo, Peicheng; Shi, Liangwei; Zhou, Junhong; Pang, Aimin
Abstract: In this work the dominant crystal faces of ϵ‐CL‐20 in vacuum was firstly obtained as (011), (10‐1), (110), (11‐1), (002), (101), (021) by the attachment energy (AE) model. Then the modified AE (MAE) model was used to predict the crystal morphologies of ϵ‐CL‐20 in five pure solvents including ethyl acetate (EA), acetone, acetonitrile, cyclohexane and methanol, and five solvent mixtures of EA/chloroform, EA/dichloromethane, EA/n‐heptane, EA/cyclohexane and EA/1‐propyl alcohol. Results demonstrate that different types of solvent and antisolvent can produce different dominant faces and the corresponding face area, consequently, affecting the crystal morphology. The effect of the volume ratio of the antisolvent to the solvent on the crystal morphologies was further investigated. Finally, the radial distribution function (RDF) of the interfacial model was used to analyze the adsorption behaviors of the solvent molecules on the CL‐20 surfaces. Abstract :